Effect of microRNA‐145 on IL‐1β‐induced cartilage degradation in human chondrocytes. Issue 14 (27th May 2014) - Yang, Bo; Kang, Xia; Xing, Yan; Dou, Ce; Kang, Fei; Li, Jianmei; Quan, Yi; Dong, Shiwu
Abstract : MicroRNA‐145 has been shown to regulate chondrocyte homeostasis. It seems that miR‐145 is implicated in cartilage dysfunction in Osteoarthritis (OA). However, the functional role of miR‐145 in interleukin‐1 beta (IL‐1β)‐induced extracellular matrix (ECM) degradation of OA cartilage has never been clarified. Here, we show that miR‐145 expression increased in OA chondrocytes and in response to IL‐1β stimulation. We confirm that mothers against decapentaplegic homolog 3 (Smad3), a key factor in maintaining chondrocyte homeostasis, is directly regulated by miR‐145. Modulation of miR‐145 affects the expression of Smad3 causing a change of its downstream target gene expression as well as IL‐1β‐induced ECM degradation in OA chondrocytes. This indicates that miR‐145 contributes to impaired ECM in OA cartilage probably in part via targeting Smad3. Abstract : The expression of miR‐145 is up‐regulated in OA chondrocytes in response to IL‐1β stimulation. Modulation of miR‐145 affected IL‐1β‐induced ECM degradation in OA chondrocytes. Smad3 is a direct target of miR‐145. MiR‐145 contributes to impaired ECM in OA cartilage probably in part via targeting Smad3.